The British Conservative Party and the state, 1929-1940 - Prescott, WJ (2020)
This thesis examines the Conservative Party’s attitude towards the role of the state between its loss of the 1929 election and the downfall of the National Government in May 1940. The appropriate extent of government intervention was one of the most important political debates in the twentieth century, and is critical to understanding the social and economic policies of a controversial decade. Despite this, how the governing Conservatives viewed the state remains neglected. Historians of 1930s Tory domestic policy have variously argued it was too interventionist, not interventionist enough, or quite reasonable. This thesis answers this question by examining an extensive range of archival and other primary sources. In doing so, it provides the first overview of the National Government’s domestic policymaking.